A foetus during labour is legally a human being. (April 2020) - Cioffi, Andrea; Cioffi, Fernanda
On 30 January 2019, in a case involving a midwife who caused the death of a foetus, the Italian Supreme Court of Cassation established that the foetus during labour, while still within the maternal womb, is a human being with all associated rights (judgment number 27539). This claim has an obvious legal consequence: anyone causing the death of a foetus during labour is guilty not of culpable abortion but of culpable homicide. This ruling paves the way for legal and bioethical debate aimed at establishing the precise moment when a foetus is no longer a potential human being but an actual human being. The consequences of this ruling will also be evident in the debate on abortion.